Electroencephalography-based neural indicators of texture preference for cosmetic formulations - Cheon, Hye-Ran; Kwon, Gusang; Kim, Youngkyung; Kim, Hyunjung; Lee, Hae Kwang; Shin, Jin Hee; Yu, Joomi; Hwang, Han-Jeong (Frontiers in Neuroscience, 2025)
This study investigated the correlation between subjective preferences for different cosmetic formulations and brain activity measured using electroencephalography (EEG). EEG data were collected from 29 participants when they applied three positive and one negative cosmetic formulation to the inside of their left forearms. According to the questionnaire results, the negative formulation showed significantly lower preference scores than the positive formulations. Additionally, significant EEG-preference correlations were consistently found in the delta and alpha bands within the sensorimotor areas closely related to tactile processing and its emotional regulation. In particular, stronger correlations were observed when only the two positive formulations with higher preferences were included in the analysis or when specific frequency bands showing significant results were combined together. These findings demonstrate the potential of predicting cosmetic preferences based on EEG data and highlight the crucial role of texture sensation in shaping user choice.